2007
DOI: 10.1634/stemcells.2007-0476
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Culture of Human Cord Blood Hematopoietic Stem/Progenitor Cells Adversely Influences Their Distribution to Other Bone Marrow Compartments After Intra-Bone Marrow Transplantation

Abstract: Intra-bone marrow injection is a novel strategy for hematopoietic stem cell transplantation. Here, we investigated whether ex vivo culture of cord blood hematopoietic stem/ progenitor cells influences their reconstitution in bone marrow after intra-bone marrow transplantation. Freshly isolated AC133؉ cells or cells derived from AC133 ؉ cells cultured with cytokines (stem cell factor, flt-3 ligand, and thrombopoietin) for 5 days were injected into the bone marrow of the left tibia in irradiated NOD/SCID mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…We found that levels of engraftment were consistently higher in the injected bone, for both fresh and cytokine‐cultured hCD34 + cells (Fig E). Lower engraftment in non‐injected bones has also been observed for CB CD34 + cells (Yamamura et al , ), but here the inability to colonize non‐injected bones appears to accentuate the engraftment defect of MPB cells cultured in cytokines (Fig E).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We found that levels of engraftment were consistently higher in the injected bone, for both fresh and cytokine‐cultured hCD34 + cells (Fig E). Lower engraftment in non‐injected bones has also been observed for CB CD34 + cells (Yamamura et al , ), but here the inability to colonize non‐injected bones appears to accentuate the engraftment defect of MPB cells cultured in cytokines (Fig E).…”
Section: Resultssupporting
confidence: 71%
“…These data indicate that the observed engraftment defect of cultured hCD34 + cells is related, at least partly, to reduced anchorage within appropriate BM niches. Of note, Yamamura et al () observed, using AC133 + CB cells, that 5‐d culture in cytokines did not impair engraftment in injected tibiae, but that cultured cells had a reduced ability to colonize non‐injected bones, in comparison with fresh cells. In the case of MPB CD34 + cells, ex vivo culture appears to impair both lodgment in injected sites, as well as homing to non‐injected bones, thus accentuating the reduced engraftment potential of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…and IBM-II HSCT. Several comparative studies that used different conditioning regimens as well as different species indicated that IBM HSCT facilitate the early engraftment [24][25][26]. In addition, higher levels of donor chimerism were observed in comparison with i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of MSC co-culturing on HSC adhesion molecule expression was assessed, as cytokines increased the expression of several HSC adhesion molecules, including the counterreceptors for VCAM-1 and fibronectin [3,4]. Co-culturing HSC with MSC did not significantly modify cytokine-induced changes in HSC CD49d (VLA-4 a-chain), CD49e (VLA-5 achain), CD44 and CD54 expression ( Fig.…”
Section: The Increase Of Cytokine-induced Cd11a In Hsc Was Prevented mentioning
confidence: 99%
“…HSC cytokine expansion has failed to improve transplantation success rates; this finding has been correlated with a loss of ''stemness'' that takes place after HSC division [1]. However, evidence of reduced cytokinestimulated HSC repopulating ability prior to cell division [2] and high engrafting levels in directly injected cytokineexpanded HSC into the bones points to a homing defect rather than just a differentiation event [3].…”
Section: Introductionmentioning
confidence: 99%